(untitled) (Latakia University Journal -Medical Sciences Series, 2022)
Green chemistry has had a lot of attention in recent years, and searching for green agents has become a need. Plants have always been a renewable reservoir of active ingredients, especially polyphenols that are famous for their antioxidant effect. We studied the reducing capacity of the aqueous extracts of some abundant plants in the Syrian coast (Citrus sinensis peels, Citrus limone peels, Olea europea leaves, Laurus nobilis leaves). The scavenging activity of the DPPH (2,2 diphenyl 1, picrylhydrazyl) free radical was measured for the four extracts. All extracts showed a good antioxidant activity and significant differences between them were observed. Bay and olive leaves extracts were superior to the other extracts, so we calculated their (IC50) concentration; there was no significant differences between the two extracts. Results were discussed according to the chemical structure of the most abundant polyphenols in each extract and structure-activity relationship. To sum up, all four aqueous extracts may be considered as good green reductants mainly bay and olive leaves extracts.